Поверхнева рекомбінація циркулярних екситонів у гіротропних кристалах і наноструктурах - Довгий, Я. (Праці наукового товариства ім. Шевченка, 2011)
The degree of circular polarization for the luminescence lines in the gyrotropic sodium uranyl acetate crystals is investigated. It is established that this parameter is smaller than the degree of circular dichroism for resonance lines. Partial depolarization of luminescence is explained on the basis of the recombination mechanism of circular excitons on the surface defects. It is shown that in the case of nanocrystals depolarization is mainly defined by the quantum dimensional changes of dielectric function and does not depend on parameters of surface roughness.